Designing Finance Structures to Satisfy Equity and Adequacy Goals - King, Richard A.; Swanson, Austin D.; Sweetland, Scott R. (Education Policy Analysis Archives, 2005)
In addition to setting high standards for student performance, educational policies must consider what resources are essential to provide an adequate educational program to meet all students' learning needs. Policy makers also want to ensure that educators make efficient use of available resources. In this exploration of school finance policy, we advance a conception of adequacy as the ideal state of vertical equity, examine the evolution of this concept through judicial reviews, and discuss methods for determining the level of funding required to achieve adequacy. We then discuss economic and political problems inherent in institutional inefficiencies that are likely to derail efforts to raise achievement in poorly performing schools even after granting them an adequate level of resources. The paper concludes with a description of how a state funding formula might provide a foundation for adequacy in all districts.